The Influence of Profitability, Investment Decisions and Dividend Payment Policy on Company Value (Study of Energy Sector Companies for the 2019-2023 period) - Lorensha, Selvi; Hertina, Dede (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The aim of this study is to confirm the effect of Profitability, Invesment Decision and Dividend Payment policy on Company Value on Sector Energy. These are quantitative researchs using explanatory to explain the relation or impact between variables. There were 88 Companies sector Energy listed on Indonesia Stock Exchange as the populations, and we selected 18 companies using purposive sampling to meet its purpose. Secondary data were gained from the annual report from each sector Energy companies ranging from 2019 until 2023 allowing them to be reviewed through multiple linear regression analysis. The resulted research showed that profitability which proxied by ROE has significant influence on firm value, Investment Decision which proxied by PER also has significant influence on firm Value however Dividen Payment Policy which proxied by DPR has no influence on firm value